Effect of Ice Bag Application to Femoral Region on Pain in Patients Undergoing Percutaneous Coronary Intervention - Sevda Korkut Bayındır; Gülsüm Nihal Çürük; Abdurrahman Oguzhan (Pain Research and Management)
Aims. The aim of this study is to determine the pain reduction effectiveness of ice bag applications to the femoral region in patients undergoing percutaneous coronary intervention. Material and Methods. A randomized controlled trial with repeated measures and two-group design. The study was completed with a total of 104 patients who met the inclusion criteria: 52 each in the experimental group and the control group. The pain experienced by the patients was evaluated before and during removal and again while the nurse applied pressure on the catheter site after removal. The NRS scores were identified as NRS1, NRS2, and NRS3 for the three assessment, respectively. Results. The NRS1 score was similar between the two groups. It increased at the 2nd measurement, and a statistically significant difference was determined between the two groups (4.0 (3.0-4.0) in the experimental group and 6.0 (4.0-7.0) in the control group) (p<0.001). Conclusions. The results of the study revealed that ice bag application to femoral region was effective in reducing pain induced by femoral catheter removal in patients undergoing percutaneous coronary intervention. Local ice bag application may therefore be recommended as a nursing intervention for pain control in such cases.